БАГАТОКРИТЕРІАЛЬНІ ЗАДАЧІ В ЕНЕРГЕТИЦІ ТА МЕТОДИ ЇХНЬОГО РОЗВ'ЯЗАННЯ НА ОСНОВІ ТЕОРІЇ НЕЧІТКИХ МНОЖИН - Екєль, П.Я.; Кокшенєв, І.В.; Перейрас, З.Щ.; Алвес, Г.В.; Перейра, Й.Г.; Соуза, П.М.Н. (Інститут електродинаміки НАН України, Київ, 2014)
The results of research into the use of models and methods of multicriteria decision making in a fuzzy environment for solving power engineering problems are presented. Two general classes of models related to multiobjective (<X, M> models) and multiattribute (<X, R> models) problems as well as methods of their analysis based on the application of the Bellman-Zadeh approach to decision making in a fuzzy environment and techniques of fuzzy preference modeling, respectively, are briefly considered. A review of the authors’ results associated with the application of these models and methods for solving diverse types of problems of power system and subsystems planning, operation, and control is presented. The recent results on the use of <X, M> and <X, R> models and methods of their analysis for the allocation of reactive power sources in distribution systems and for the prioritization in maintenance planning in distribution systems, respectively, are considered. References 35, table 1.